The Impact of Tourists' Misbehavior on the Tourism Economy in Bali: A Case Study and Economic Analysis - I Nengah Alit Nuriawan; Ni Putu Yeni Ari Yastini (Samā Jiva Jnānam (International Journal of Social Studies), 2023)
The portrayal of tourists' misbehavior via social media and news channels has emerged as a significant factor shaping Bali's tourism economy. Predominantly fueled by these digital platforms, negative depictions of tourists' misconduct influence perceptions and potentially disrupt Bali's tourism landscape. This study explores the intricate interplay between these portrayals and their tangible effects on the island's economic sustainability. The impact of negative portrayals manifests in various dimensions within Bali's tourism economy. Firstly, these depictions wield the potential to dissuade potential tourists, resulting in a decline in tourist arrivals. Consequently, a reduction in visitor numbers directly impacts the island's tourism revenue, affecting diverse sectors reliant on tourism expenditure, such as hospitality, accommodations, local businesses, and employment opportunities. An in-depth economic analysis reveals the consequential aftermath of decreased tourism revenue. Bali's economy faces challenges encompassing diminished government income, reduced investments, and the potential destabilization of livelihoods for communities dependent on the tourism sector. Strategic mitigation strategies emerge as imperative in addressing these economic implications. The study advocates for the adoption of responsible tourism practices, the restoration of Bali's positive image, economic diversification initiatives, and investments in alternative income sources beyond tourism. In conclusion, the abstract underscores the profound influence of negative portrayals of tourists' misbehavior on Bali's tourism economy. By analyzing the tangible economic consequences and advocating for sustainable strategies, Bali aspires to mitigate the adverse effects, fostering a resilient and diversified economy capable of withstanding disruptions in the tourism sector while ensuring sustainable growth and prosperity